GAS CHROMATOGRAPH-MASS SPECTROMETER ANALYSIS AND ACUTE ORAL TOXICITY OF CINNAMOMUM BURMANNII., NESS EX BL. ESSENTIAL OIL - W, HERDWIANI; Aa, Soemardji; El-fahmi; Mi, Tan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Cinnamomum burmannii Nees Ex Bl. essential oil has cytotoxic effect on a lot of cancer cell lines. An investigation was carried out to analyze the possible chemical components from C. burmannii essential oil and evaluate its acute toxicity, before an effective formulation of C. burmannii essential oil as anticancer drugs. Methods: This study was analyzed chemical components from C. burmannii essential oil by gas chromatograph-mass spectrometer (GC-MS) and evaluated the acute oral toxicities of C. burmannii essential oil in strain Balb/C mice. Results: This analysis revealed that C. burmannii essential oil contains the active compound cinnamaldehyde (71.814%), trans-cinnamyl acetate (11.09%), coumarin (3.41%), and cineol (1.77%). Acute oral toxicity of C. burmannii essential oil with lethal dose 50 3679.11 mg/kg BW. Conclusion: C. burmannii essential oil contains the active compound cinnamaldehyde, trans-cinnamyl acetate, coumarin and cineol. Acute oral toxicity conclusively indicates C. burmannii essential oil includes category 5 practically non-toxic. Keywords: Gas chromatograph-mass spectrometer, Cinnamomum burmannii, Essential oil, Acute toxicity.